Challenges of Education Management in the Disruptive Change Era of School Administrators. - Perathoranich, Chatchaya (Journal of Inclusive and Innovative Education, 2020)
This paper aims to discuss the significance and understanding of educational management challenges in disruptive change era faced by school administrators. There are four main school administrators’ attributes: 1) characteristics of school administrators in the new era, 2) role and duty, 3) modern technology, 4) moral and ethics. School administrators should have positive attitudes towards digital technology, change of working styles, manpower, curriculum, learning process, materials development, measurement and evaluation, innovation, learning management, encouragement for teachers to become a coach entitled ‘3Es’.Factors that strive to success are 1) engagement, 2) empower, 3) moral and ethics. Digital technology has played a vital role in education; therefore, school administrators should be more aware of its effects on education and learning management, along with having morality and ethics.